Institutional Mechanisms of Land Development Management (Economics and region, 2020)
A new institutional and neo-institutional theory theoretical apparatus in the field of land economy are revised and the necessity for further land development institutionalization in Ukraine is determined. Social economic relations are analyzed. It is revealed that land relations have an essential structure: in the form of an institutional complex, based on the traditional, customary and religious norms of individuals behavior, as well as social, political, economic, legal and other institutions, as stable socio-economic, organizational and legal structures, institutions and organizations. The main principles of new institutional and neo-institutional economy in the land sphere are determined, namely institute-centrism, limited rationality, historicism, economic opportunism, land good. The relationship nature of land relations institutionalization means with peculiarities of state financial and economic space formation in the author's interpretation is considered at the development level in Ukraine of land circulation institutional infrastructure, The State Land Bank and the National Land Fund formation as state institutions. It has been found that evolutionary institutional changes are inherent in social land development when partial peripheral gradual changes in rules and regulations cause gradual changes and land development. It is proved that state, having administrative advantages, acting by economic methods and methods of legal influence, should change and adapt the institutional environment, as a set of rules, norms that form the basis of production, exchange and redistribution in the land sphere, because the main link in the bundle of land rights, belongs to the people of Ukraine.
Keywords: land development; institute; institutional economy; methodology; land economy; rent relations; ecological rent